Extreme precipitation events and their relationship with ENSO and MJO phases over northern South America. (14th October 2016) - Shimizu, Marília Harumi; Ambrizzi, Tércio; Liebmann, Brant
ABSTRACT: Several droughts and floods in Amazonia and Northeast Brazil have occurred in recent years and projections from Intergovernmental Panel on Climate Change indicate an increase of these extreme events. El Niño Southern Oscillation (ENSO) is one of the phenomena associated with extreme rainfall events in the Amazon. However, recent studies have indicated that the basic response of ENSO is dependent on the Madden–Julian Oscillation (MJO) phase. Hence, this study analyses the MJO influence on precipitation extreme events over northern South America in El Niño and La Niña years. Extreme precipitation events over northern South America for the rainy season (December–May) were obtained through a composite analysis of the combinations of ENSO and MJO phases. Most of the dry extreme events occurred during El Niño periods, while wet extreme events were more recurrent during La Niña or neutral years. However, the results showed that the MJO convection could enhance or weaken the basic response of ENSO on extreme precipitation events. Moreover, dry/wet extreme events over both Amazon and Northeast Brazil are favoured when MJO convection over Indonesia is enhanced (MJO phases 4 and 5)/suppressed (MJO phase 2). Additionally, the interannual variability of the extreme events showed an increasing linear trend for dry extreme events and a decreasing linear trend for wet extreme events. The results presented here contribute to a better understanding of the climate variability and will be helpful for the forecast of ENSO effects on extreme events over northern South America.